Kajian Gap Pertumbuhan Ekonomi Pulau Jawa Antara Kondisi Pandemi dengan Ideal Tahun 2020 - Ilham Pramadhitya Firdaus; Santy Paulla Dewi (Jurusan Perencanaan Wilayah dan Kota, 2023)
In 2020, the world is faced with an outbreak of a new virus known as COVID-19 that affects almost all aspects of life, including the economy. COVID-19 is proven to decrease the rate of world economic growth, including on Java Island in Indonesia (at the end of 2020, it contracted to -3,39% and become the their most affected year). The focus of this research is to identify and analyze the gap between economic growth in pandemic and ideal economic growth on the 119 regencies/cities of Java Island in the period of 2020. This secondary-based data and quantitative-method research goes through three stages: (1) identifying economic growth during pandemic 2020, (2) forecasting and identifying the ideal economic growth in 2020, and (3) Analyzing and classifying the gap between economic growth during pandemic and ideal condition in 2020. The results showed that there was a significant gap between those two conditions with the range of 1,22% - 16,09%. the majority of districts and cities in Java experienced a moderate decline in economic growth of 73.95%. The regencies/cities that experienced an insignificant decline were around 8.40% and a significant and very significant decline occurred in 17.65% of regencies and cities on the island of Java.